2020
DOI: 10.3390/pharmaceutics12070607
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lipid–Polymer Hybrid Nanoparticles for Improving Oral Absorption of Enoxaparin

Abstract: Enoxaparin, an anticoagulant that helps prevent the formation of blood clots, is administered parenterally. Here, we report the development and evaluation of lipid–polymer hybrid nanoparticles (LPHNs) for the oral delivery of enoxaparin. The polymer poloxamer 407 (P407) was incorporated into lipid nanoparticles to form gel cores and ensure high encapsulation efficiency and the controlled release of enoxaparin. In vitro results indicated that 30% of P407 incorporation offered higher encapsulation effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The poor biological concentration of PP suspension was achieved due to poor absorption from the small intestine, which corresponds to the very poor solubility of PPN in the intestinal milieu. On the other hand, the absorption and biological concentration after oral administration of the optimized PPN-LPHNPs was ascribed to the higher surface area for intestinal absorption, the presence of PPN in the amorphous state in the matrix of LPHNPs, and the controlled release of PPN from the unique hybrid matrix of LPHNPs [ 51 , 52 ]. Furthermore, the mucoadhesive characteristic of the optimized PPN-LPHNPs is another major factor behind the higher oral absorption of PPN.…”
Section: Resultsmentioning
confidence: 99%
“…The poor biological concentration of PP suspension was achieved due to poor absorption from the small intestine, which corresponds to the very poor solubility of PPN in the intestinal milieu. On the other hand, the absorption and biological concentration after oral administration of the optimized PPN-LPHNPs was ascribed to the higher surface area for intestinal absorption, the presence of PPN in the amorphous state in the matrix of LPHNPs, and the controlled release of PPN from the unique hybrid matrix of LPHNPs [ 51 , 52 ]. Furthermore, the mucoadhesive characteristic of the optimized PPN-LPHNPs is another major factor behind the higher oral absorption of PPN.…”
Section: Resultsmentioning
confidence: 99%
“…As a classical antithrombotic, aspirin showed a protective effect by 50-80% at a dose of 20 mg/kg and above [44][45][46]. Tang et al discovered that the protective effect of enoxaparin-loaded LPHN2 was 50.0%, 2.99-fold higher than that of enoxaparin solution (16.70%) after oral administration, indicated that lipid-polymer hybrid nanoparticles are effective in improving oral absorption and the inhibition effect of enoxaparin against thrombin-induced thrombosis [14]. Furthermore, the Viscera index can be used to detect pathological changes in animals [47].…”
Section: Discussionmentioning
confidence: 99%
“…Polymer-and lipid-based nanocarriers, such as polymeric micelles, polymeric nanoparticles, lipid nanocapsules, microemulsions, and solid lipid nanoparticles, have been investigated to improve the HP oral absorption [13][14][15][16][17]. Chitosan and alginate biopolymers have received significant attention in this context because of their non-toxic, biocompatible, and biodegradable properties [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, LNPs defend mRNA from degradation by enzymes from the endosome [ 112 ]. The characteristic guarantees high encapsulation efficiency [ 113 ]. On the other hand, LNPs have good biocompatibility through a series of biological processes to deliver mRNAs for expression.…”
Section: Delivery Strategies Of Mrna Vaccinesmentioning
confidence: 99%
“…The first process involves the apolipoprotein E (ApoE)-low density lipoprotein receptor (LDLR) pathway. This endogenous pathway is a targeting foundation for efficient delivery [ 113 ]. Then, the TLR4-mediated endocytosis takes up LNPs, forming a vesicle to fuse with endosomes [ 114 ].…”
Section: Delivery Strategies Of Mrna Vaccinesmentioning
confidence: 99%